WAYS OF IMPROVING ADMINISTRATION LOCAL TAXES - Elena V. Egorova (Статистика и экономика)
The article is devoted to the administration of taxes payable to the municipalities (the local budget). The study also identified the role of local taxes in the budgets of municipalities, the problems of administration of local taxes and the ways of their solution